EXAMINING THE RELATIONSHIP BETWEEN CUSTOMER ENGAGEMENT AND BRAND ADVOCACY IN DIGITAL PLATFORMS - Supriatna, Ucu; Riana, Nia; Aripin, Zaenal (Organisasi Kreatif Indonesia Emas, 2025)
Background:With the increasing prominence of digital platforms in modern marketing, customer engagement has become a key driver of brand success. The role of customer engagement in fostering brand advocacy, particularly through the use of digital platforms, has garnered significant attention. One of the most influential factors in this process is user-generated content (UGC), which has been shown to impact brand perceptions and customer behavior. Aims:This study aims to explore the relationship between customer engagement behaviors on digital platforms and brand advocacy, with a particular focus on the role of emotional connection and user-generated content. The research seeks to identify the key factors that influence customer engagement and how these behaviors contribute to brand advocacy, thereby providing insights into effective digital marketing strategies. Research Method:A mixed-methods approach was employed, combining both qualitative and quantitative research methods. Data was collected through surveys and interviews with digital platform users, analyzing their engagement behaviors, emotional connections with brands, and the impact of user-generated content on brand advocacy. The data was then analyzed using statistical methods to identify patterns and correlations. Results and Conclusion:The study found that active customer engagement behaviors, such as commenting and sharing content, were strongly correlated with higher levels of emotional connection to the brand, which in turn increased the likelihood of brand advocacy. User-generated content, particularly positive reviews and social media posts, served as a powerful form of social proof, influencing other customers to trust and engage with the brand. Brands that leveraged personalized content, community-building tools, and influencer collaborations saw higher levels of customer engagement and advocacy. Contribution:This research contributes to the growing body of knowledge on customer engagement and brand advocacy by providing a comprehensive analysis of the factors that drive advocacy behaviors on digital platforms. It highlights the importance of emotional connection, UGC, and platform features in shaping customer perceptions and loyalty. The findings offer valuable insights for brands seeking to enhance their digital marketing strategies and foster long-term customer loyalty.